An Analysis Of Students’ Difficulties In Using Past Tense In Writing Narrative Text At SMK Negeri 3 Medan - Putri Purnama Sihaloho; Sahlan Tampubolon; Ernawati Tampubolon (Lembaga Riset dan Inovasi Almatani, 2026)
This study aimed to analyze students’ difficulties in using the simple past tense in writing narrative texts at SMK Negeri 3 Medan. The research focused on identifying the types of grammatical errors and exploring the factors contributing to these difficulties. A descriptive qualitative research design was employed. The participants were tenth-grade students of the Rekayasa Perangkat Lunak program. Data were collected through a writing test and semi-structured interviews and were analyzed using data condensation, data display, and conclusion drawing techniques. The findings revealed that students experienced significant difficulties in forming regular and irregular verb forms, using the past forms of “to be” (was/were), and maintaining tense consistency throughout their narratives. The errors were primarily influenced by limited vocabulary mastery, insufficient understanding of grammatical rules, lack of structured practice, and low learning motivation. These findings indicate that students’ grammatical competence significantly affects their narrative writing performance. Therefore, contextualized grammar instruction, systematic explanation of verb forms, and continuous guided writing practice are essential to enhance students’ mastery of the simple past tense and improve their overall writing proficiency.